Glucose‐Responsive Composite Microneedle Patch for Hypoglycemia‐Triggered Delivery of Native Glucagon. Issue 30 (5th June 2019) - GhavamiNejad, Amin; Li, Jason; Lu, Brian; Zhou, Liwei; Lam, Loretta; Giacca, Adria; Wu, Xiao Yu
Abstract: Insulin‐dependent patients with diabetes mellitus require multiple daily injections of exogenous insulin to combat hyperglycemia. However, administration of excess insulin can lead to hypoglycemia, a life‐threatening condition characterized by abnormally low blood glucose levels (BGLs). To prevent hypoglycemia associated with intensive insulin therapy, a "smart" composite microneedle (cMN) patch is developed, which releases native glucagon at low glucose levels. The cMN patch is composed of a photo‐crosslinked methacrylated hyaluronic acid (MeHA) microneedle array with embedded multifunctional microgels. The microgels incorporate zwitterionic moieties that stabilize loaded glucagon and phenylboronic acid moieties that provide glucose‐dependent volume change to facilitate glucagon release. Hypoglycemia‐triggered release of structurally unchanged glucagon from the cMN patch is demonstrated in vitro and in a rat model of type 1 diabetes (T1D). Transdermal application of the patch prevented insulin‐induced hypoglycemia in the diabetic rats. This work is the first demonstration of a glucose‐responsive glucagon‐delivery MN patch for the prevention of hypoglycemia, which has a tremendous potential to reduce the dangers of intensive insulin therapy and improve the quality of life of patients with diabetes and their caregivers. Abstract : A "smart" composite microneedle patch is designed for delivering an insulin‐counterregulatory hormone, glucagon, in response to hypoglycemia (low blood sugar levels) in diabetic subjects. This system exploits the multifunctionality of embedded polymeric microgels that are optimized to stabilize and encapsulate native glucagon and for hypoglycemia‐triggered glucagon release.